Variabilidade espaço-temporal da fenologia da vegetação na transição do Cerrado e Pantanal mato-grossense - Moraes, Tonny Jader de (2019)
Rational use and conservation of natural resources depend on monitoring, characterization and understanding of the phenological dynamics of vegetation. With frequent and long-term satellite observations, it is possible to monitor changes and characteristics of surface phenology. Thus, the objective of this work is to contribute to the understanding of the phenological variability of the vegetation and its relationship with rainfall seasonality in the transition regions of Pantanal and Cerrado Mato-grossense along latitudes -15º to -18º. Landsat satellite images and TRMM weather radar data were used to obtain precipitation time series and the NDVI vegetation index. Precipitation data were obtained from the National Aeronautics and Space Administration (NASA) Giovanni platform, from the National Meteorological Institute (INMET) and the National Water Agency (ANA) network weather stations and the NDVI vegetation index was collected from Landsat 05 and 08 satellite data were obtained from the US Geological Survey (USGS). The results revealed lower precipitation intensity in the latitudes that comprise the Pantanal and greater variability in the dynamics of the Cerrado vegetation phenology. In addition, phenological patterns varied according to the characteristics of each region, with changes in surface use and occupation. Finally, the trends observed by phenological parameters differed throughout the Cerrado and Pantanal transition. In addition, rainfall appears to have a greater influence on phenological variability in native vegetation areas and agricultural lands in the Cerrado than in the Pantanal. With the results of this research it was possible to characterize spatially and temporally the variability of the vegetation phenology of the transition between the Cerrado and Pantanal, through the maps and graphs, which can provide a representation of the surface phenology and can serve as an alternative to fill other gaps of vegetation region research.